Persuasive Strategies in Greta Thundberg Speech During Campaign with Theme Climate Change - sri wahyuni; Ulfatmi Azlan; chandri febri santi (English Language, Linguistics, Literature, And Education Journal, 2022)
The aims of this research are: (1) To find out the types of persuasive strategies are used by Greta Thunberg in her speeches with theme climate change, (2) To describe persuasive strategies are applied by Greta Thunberg in her speeches with theme climate change. By using qualitative method, the researcher felt easy to analyze the speech and the researcher will have right answer about the question. The writer used documentation technique for collecting data. The writer used content analysis for technique of analysis. The writer found three persuasive strategies that used by Greta Thundberg Speech During Campaign With Theme Climate Change. There are : forensic rhetoric, demonstrative rhetoric, deliberative rhetoric. There are 4 forensic rhetoric , 4 demonstrative rhetoric, 11 deliberative rhetoric. The writer found all of ways that used by Greta Thundberg Speech During Campaign With Theme Climate Change. There are : Appeal to Emotion, showing evidences, personal character of the speaker. There are 5 Appeal to Emotions(ethos), 9 showing evidences(logos), 7 personal characters of the speaker.